The Translation of Idioms in George Orwell’s Animal Farm - Husnul Abdi; Aris Munandar (Lexicon, 2019)
This research aims to study the use of idioms in Animal Farm (1954) and their translation into Bahasa Indonesia. The idioms found in the original text are classified based on the classification of idioms by Adam Makkai (1972). The idiom translation strategy is identified by comparing the idioms in the source text to the translation in the target text. The research identifies 156 idioms and classifies them into phrasal verb idioms (39%), tournure idioms (34%), irreversible binomials (11%), phrasal compound idioms (14%), and incorporating verb idioms (2%). There are 4 strategies to translate an idiom following Mona Baker (1992) and 1 strategy following Newmark (1991). The idiom translation strategy is classified into translating an idiom by using an idiom of similar meaning and form (1.92%), translating an idiom by using an idiom of similar meaning but different form (1.92%), translating an idiom by using paraphrase (85.90%), translating an idiom by using omission (0.64%), and literal translation strategy (9.62%).